Une ethnologue parmi des enfants qui grandissent en Chine urbaine - Gladys Chicharro (Ateliers d'Anthropologie)
This article looks back at long-term research conducted since 2001 in what was then a small “new town” in Hebei province, but in one decade became simply a suburb of the capital. In a rapidly changing urban environment, I evoke field relationships that are established and then evolve in a quickly changing urban environment, between an ethnologist and family members who grow up, age, and change status and generation in parallel. Those regular returns and the positioning readjustments they entail bring different perspectives for analysing the changes that the families have lived through, particularly due to the one-child policy, its abrogation, intergenerational relations, and the evolution of the place of children in urban Chinese society.